Calf Compression Sleeves Change Biomechanics but Not Performance and Physiological Responses in Trail Running - Kerhervé, Hugo A.; Samozino, Pierre; Descombe, Fabrice; Pinay, Matthieu; Millet, Guillaume Y.; Pasqualini, Marion; Rupp, Thomas (Frontiers in Physiology, 2017)
Introduction: The aim of this study was to determine whether calf compression sleeves (CS) affects physiological and biomechanical parameters, exercise performance, and perceived sensations of muscle fatigue, pain and soreness during a prolonged (~2 h 30 min) outdoor trail running. Methods: Fourteen healthy trained males took part in a randomized, cross-over study consisting in two identical 24-km trail running sessions (each including one bout of running at constant rate on moderately flat terrain, and one period of all-out running on hilly terrain) wearing either degressive CS (23 ± 2 mmHg) or control sleeves (CON, < 4 mmHg). Running time, heart rate and muscle oxygenation of the medial gastrocnemius muscle (measured using portable near-infrared spectroscopy) were monitored continuously. Muscle functional capabilities (power, stiffness) were determined using 20 s of maximal hopping before and after both sessions. Running biomechanics (kinematics, vertical and leg stiffness) were determined at 12 kmh-1 at the beginning, during, and at the end of both sessions. Exercise-induced Achilles tendon pain and delayed onset calf muscles soreness (DOMS) were assessed using visual analogue scales. Results: Muscle oxygenation increased significantly in CS compared to CON at baseline and immediately after exercise (p < 0.05), without any difference in deoxygenation kinetics during the run, and without any significant change in run times. Wearing CS was associated with (i) higher aerial time and leg stiffness in running at constant rate, (ii) with lower ground contact time, higher leg stiffness, and higher vertical stiffness in all-out running, and (iii) with lower ground contact time in hopping. Significant DOMS were induced in both CS and CON (> 6 on a 10-cm scale) with no difference between conditions. However, Achilles tendon pain was significantly lower after the trial in CS than CON (p < 0.05). Discussion: Calf compression did not modify muscle oxygenation during ~2h30 of trail running but significantly changed running biomechanics and lower limb muscle functional capabilities toward a more dynamic behavior compared to control session. However, wearing compression sleeves did not affect performance and exercise-induced DOMS, while it minimized Achilles tendon pain immediately after running.